Identifikasi Komponen, Faktor dan Resiko Relatif yang Berpengaruh pada Hasil Inseminasi Buatan pada Sapi Bali - Rodiah Rodiah; Enny Yuliani; Chairussyuhur Arman; Adji Santoso Dradjat (Jurnal Ilmu Dan Teknologi Peternakan Indonesia (JITPI) Indonesian Journal of Animal Science and Technology), 2016)
The aims of the research were to identify components, factors and relative risk (Odd ratio) which may influencethe artificial insemination results. The study were performed in two villages those were Kuranji and Tanah Beak,by identification of components and factors which may contribute to successful artificial insemination results,then the flow chart of successful and obstacle were designed. Based on the flow chart survey was performed to thefarmers and inseminators. Parameters evaluated were factors may influence of the result of insemination such as;management, oestrus detection by farmers and insemination by inseminators. The data was tabulated and analisedusing epidemiology analysis of odd ratios (OR). The results showed that insemination results of Kuranji villagedo not have the risk to be not pregnant as the odd ratio was less than 1 (OR <1,0), with the range of 0,10 to 0,20.While artificial insemination in Tanah Beak village showed risk of cows to be infertile or non pregnant relativelyhigher with OR higher than 1 (OR> 1.0), with the range of 1,5 to 2,0. The results showed that the risk to beunsuccessful to produce pregnancy were caused by oestrus detection, feeding management, skill inseminator andexperience of farmers. Finally it can be concluded that oestrus detection by farmers, feeding management,insemination by inseminator and experience of farmers may contribut to the high risk fail to produce pregnancyusing artificial insemination in Tanah beak village.